1999
DOI: 10.1211/0022357991772899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Antidepressants on Glycaemia and Insulin Levels of Normoglycaemic and Alloxan-induced Hyperglycaemic Mice

Abstract: Depression is an important problem among diabetic patients. We have investigated the effect of some antidepressant drugs on plasma glucose and insulin levels in normoglycaemic and alloxan-induced diabetic mice. For this purpose the effects of nortryptiline (as an example of a tricyclic antidepressant) and fluoxetine and sertraline (as examples of selective 5-HT re-uptake inhibitors) were examined on plasma glucose and insulin levels. Nortryptiline significantly increased glucose levels and reduced insulin leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 10 publications
(17 reference statements)
2
31
2
Order By: Relevance
“…The administration of sertraline reduces glycemia in fasting diabetic mice (14) and decreases fasting and glucose overload glycemia in diabetic and non-diabetic rats (12). However, in the present study, insulinemia was increased by sertraline treatment only after glucose overload.…”
contrasting
confidence: 75%
“…The administration of sertraline reduces glycemia in fasting diabetic mice (14) and decreases fasting and glucose overload glycemia in diabetic and non-diabetic rats (12). However, in the present study, insulinemia was increased by sertraline treatment only after glucose overload.…”
contrasting
confidence: 75%
“…First, because the circulating 5-HT concentrations rose, it is possible that 5-HT had a direct effect to reduce glucose uptake by muscle, the predominant insulin-responsive peripheral tissue involved in glucose disposal in the dog. This explanation seems unlikely, however, because peripheral administration of the 5-HT precursor 5-hydroxytryptophan or various selective serotonin reuptake inhibitors to monoamine oxidase inhibitor-treated mice has a hypoglycemic rather than a hyperglycemic effect (24 -27), an action apparently independent of changes in insulin concentrations (25)(26)(27). Moreover, 5-HT Fig.…”
mentioning
confidence: 99%
“…Treatment with antidepressants can directly interfere with blood glucose levels or may interact with hypoglycemic agents. In a recent preclinical study it was demonstrated that prolonged treatment with nortriptyline increases blood glucose in diabetic and nondiabetic mice, while fluoxetine and sertraline decrease it (19). Therefore, treatment with antidepressants for diabetic individuals must consider the variability in blood glucose level control at different times and a comparison of the available antidepressant agents is recommended.…”
Section: Introductionmentioning
confidence: 99%